P033 Single-cell analysis of gut mucosal- and peripheral blood cells in ulcerative colitis patients undergoing vedolizumab treatment. (21st January 2022) - Karmi, N; Sun, S; de Jong, S; Bangma, A; Teunis, J; Paraskevopoulou, M; Juarez, J; Bleck, B; Farahmand, S; Weersma, R; Bigaeva, E; Festen, E
Abstract: Background: Vedolizumab (VDZ), a monoclonal antibody that targets α4β7 integrin, was approved to treat moderate-to-severe ulcerative colitis (UC) based on the presumption that it blocks T cell recruitment to the inflamed intestinal mucosa. The clinical evidence suggests that up to 50% of UC patients do not achieve disease remission under VDZ treatment. This study aims to identify changes in cell abundances and molecular pathways associated with VDZ response in UC. To this end, we included anti-tumor necrosis factor (anti-TNF)-naïve and anti-TNF-exposed patients with active UC, and utilized single-cell RNA sequencing (scRNAseq) and high-dimensional flow cytometry (Cytek) to assess the peripheral blood and the gut mucosal compartments. Methods: Gut mucosal biopsies from inflamed and non-inflamed regions, and peripheral blood mononuclear cells (PBMCs) were obtained from UC patients 2 wks before (t0) and 14 wks after (t4) the start of VDZ administration. Response to treatment was prospectively evaluated based on endoscopic assessment (defined as a decrease in total Mayo score between t0 and t4) and physician global assessment (PGA) that incorporates disease activity score and biochemical measurements. Results: A total of 25 UC patients (pts) were included: 44% anti-TNF-naïve. Endoscopic response to VDZ was observed in 32% of UC pts, while 56% of pts showed response based on PGA. The VDZ response rate (by PGA) was higher in anti-TNF-naïve pts vs anti-TNF-exposed pts (82% vs 36% responders, respectively). A preliminary analysis was performed on samples from 8 (out of 25) UC pts, profiling >70, 000 gut mucosal cells and >25, 000 PBMCs. Within the mucosal compartment, at t0 we identified immune cells (50% of all captured cells), stromal cells (10%), and epithelial cells (40%). Upon inflammation, the proportion of immune cells increased to 70%, stromal cells to 20%, while epithelial cells depleted to 10%. Notably, all main identified immune cell lineages – T cells, B cells and myeloid cells – contributed to the expansion of the immune cell compartment in inflamed mucosa. In line with scRNAseq data, we identified all major immune cell populations and detected expression of both the classic gut-directed and the redundant trafficking integrins by Cytek. Conclusion: The preliminary results substantiate our current understanding of VDZ biology in UC. We confirm that anti-TNF-naïve pts have a higher response rate to VDZ vs anti-TNF-exposed pts. With this unique cohort, our study has the power to further explore molecular mechanisms and pathways that underlie VDZ response at the single-cell level.